The effect of short music videos on needs satisfaction and separation anxiety of children's family members during COVID-19: The example of TikTok - Huang, Ya-Li; Chen, Yu-Kun; Lin, Shi-Hao; Cao, Hua; Chen, Qiang (Frontiers in Pediatrics, 2022)
Objective: To investigate the effect of short music videos on needs satisfaction and separation anxiety of the family members of children with congenital heart disease (CHD) in the cardiac intensive care unit (CICU) during the COVID-19 pandemic. Methods: Eighty-seven children’s family members were divided into the study group and the control group between February 2020 and March 2021. During the COVID-19 pandemic, the participants in the control group were visited by telephone, while the participants in the study group used the TikTok short music video application and WeChat as communication tools. After the intervention, the critical care family needs inventory (CCFNI) and separation anxiety scale (SAS) for all participants were recorded and analyzed. Results: There were no statistically significant differences in general characteristics or preintervention data between the two groups. However, the two dimensions of the support scale and information scale of the CCFNI in the study group were significantly different from those in the control group after the intervention (P=0.008 and P=0.021, respectively). There were significant differences in the three dimensions of the SAS between the two groups (P=0.004, P =0.007, and P=0.041, respectively). Conclusion: The visiting system of the ICU changed during the COVID-19 pandemic, and the use of the TikTok short music video application and WeChat was conducive to optimizing the CICU ward visiting process, reducing the separation anxiety of the family members of children in the CICU, and improving their needs satisfaction.